An abdominal giant lipoma that was surgically resected: case report - Fan, Jianchun; Yang, Chunbaixue; Cao, Xinran; Wu, Xueliang (Frontiers in Surgery, 2025)
BackgroundGiant retroperitoneal lipomas are rare benign tumors that frequently present with nonspecific symptoms, leading to delayed diagnosis. This case highlights the importance of multidisciplinary evaluation and surgical management in treating large retroperitoneal masses.Patient presentationA 42-year-old woman presented with right lower abdominal distension and occasional nausea. Computed tomographic (CT) imaging revealed a massive retroperitoneal fat-containing lesion (22 cm × 9.8 cm × 31 cm) compressing adjacent organs. Surgical resection via a transrectus approach removed a 4.86-kg encapsulated lipoma. Postoperative recovery was uncomplicated, and pathology confirmed a benign lipoma.ConclusionsComplete surgical excision remains the treatment of choice for giant retroperitoneal lipomas. Early imaging [CT/magnetic resonance imaging (MRI)] and differentiation from malignancies are critical. This case, representing one of the heaviest reported retroperitoneal lipomas (4.86 kg), demonstrates that curative resection is feasible for massive symptomatic masses, and contributes technical and outcome data to the limited literature on giant abdominal lipomas. It underscores the importance of long-term follow-up to monitor recurrence.